Classical codes in quantum state space. (17th November 2015) - Howard, Mark
Abstract: We present a construction of Hermitian operators and quantum states labelled by strings from a finite field. The distance between these operators or states is then simply related (typically, proportional) to the Hamming distance between their corresponding strings. This allows a straightforward application of classical coding theory to find arrangements of operators or states with a given distance distribution. Using the simplex or extended Reed–Solomon code in our construction recovers the discrete Wigner function, which has important applications in quantum information theory.